Apoptosis Effects of Dihydrokaempferol Isolated from Bauhinia championii on Synoviocytes. (2nd December 2018) - Zhang, Yuqin; Yan, Guohong; Sun, Chengtao; Li, Huang; Fu, Yanhui; Xu, Wei
Abstract : Bauhinia championii (Benth.) Benth. is a traditional medicinal plant used in China to treat rheumatoid arthritis (RA), especially in She ethnic minority group. This study focused on the active constituents from the rattan of B. championii (Benth.) Benth., which possess potential apoptosis effects. A conventional phytochemical separation method for the isolation of compounds from the ethyl acetate extract of B. championii was developed. The procedure involved extraction, liquid–liquid partitioning with ethyl acetate, and subsequent compound purification, respectively. Additionally, cell viability of dihydrokaempferol found abundantly in it was evaluated in vitro by MTS, and the antiapoptosis effect was evaluated by annexin V/PI staining (Flow Cytometry Analysis) and western blot. The results showed that nine flavonoids, and five other compounds, were isolated from the ethyl acetate extract of B. championii and were identified as β -sitosterol (1), 5, 6, 7, 3', 4', 5'-hexamethoxyflavone (2), 3', 4', 5, 7-tetrahydroxyflavone (3), 5, 7, 3', 4', 5'-pentamethoxyflavone (4), 4'-hydroxy-5, 7, 3', 5'-pentamethoxyflavone (5), apigenin (6), liquiritigenin (7), 5, 7-dihydroxylcoumarin (8), 3', 4', 5, 7, -pentamethoxyflavone (9), n -octadecanoate (10), lupine ketone (11), dibutylphthalate (12), dihydrokaempferol (13), and 5, 7, 3′, 5′-tetrahydroxy-6-methylflavanone (14). Among these compounds, 5-14 were isolated for the first time from B. championii. In addition, apoptosis effects of abundant dihydrokaempferol were evaluated in vitro . Dihydrokaempferol exhibited inhibitory effects on the proliferation of synoviocytes. Furthermore, dihydrokaempferol promoted Bax and Bad expression, as well as the cleavage of caspase-9, caspase-3, and PARP. Meanwhile, it inhibited Bcl-2 and Bcl-xL expression. These findings indicate that dihydrokaempferol isolated from the ethyl acetate extract of B. championii effectively promotes apoptosis, which is an important process through suppression of apoptotic activity. The results are encouraging for further studies on the use of B. championii in the treatment of RA.